Keperdulian al-Qurâ€™an Terhadap Masyarakat Miskin - Helfi, Helfi (Alhurriyah, 2014)
The neglect of the poor is an indicator of the governmentâ€™s failure in carrying out their functions as protectors of the people, especially in connection with the fulfillment of basic rights such as food, clothing, housing, education and health. The emergence of the poor society is not merely a failure of the lowÂlevel society, but also as the impact of uneven distribution policy. Rasul and his companions through their monetary policy provide economic protection for the poor from various country incomes. The sensitivity of poverty was not only shown for the Islamic society but also nonÂIslamic groups who needed help. Various programs of â€œantiÂpovertyâ€ were conducted as a manifestation to protect the lower class.